Tutor auditory memory for guiding sensorimotor learning in birdsong - Yazaki-Sugiyama, Yoko (Frontiers in Neural Circuits, 2024)
Memory-guided motor shaping is necessary for sensorimotor learning. Vocal learning, such as speech development in humans and song learning in bird juveniles, begins with the formation of an auditory template by hearing adult voices first, followed by a period of vocal matching to the memorized template using auditory feedback. In zebra finches, the widely used songbird model system, only males develop individually unique stereotyped songs. The production of normal songs relies on auditory experience of tutor's songs (commonly their father's songs) during a critical period in development that consists of orchestrated auditory and sensorimotor phases. "Auditory templates" of tutor songs are thought to form in the brain to guide later vocal learning, while formation of "motor templates" of own song has been suggested to be necessary for the maintenance of stereotyped adult songs. Where these templates are formed in the brain and how they interact to guide song learning, presumably with template-matching error correction, remains to be clarified. Here, we review and discuss studies on auditory and motor templates in the avian brain. We suggest that distinct auditory and motor template systems exist that switch their functions during development.